Opportunistic Cryptococcal Antigenemia in the HAART Era at HIV Epidemic Settings of Northwest Ethiopia. (7th September 2020) - Negash, Markos; Wondmagegn, Tadelo; Tajebe, Fitsumbrhan
Abstract : Background . Cryptococcus neoformans is a frequent opportunistic infection in patients with the acquired immunodeﬁciency syndrome. While the advent of ART reduces the occurrence of cryptococcal meningitis in HIV patients, cryptococcal disease remains a leading cause of morbidity and mortality in the developing world especially in sub-Saharan Africa which is the epicenter of HIV. This study aimed to assess the cryptococcal antigenemia, CD4+ Th cell counts, HIV RNA viral load, and clinical presentations among HIV-positive patients in Northwest Ethiopia. Method . A total of two hundred (200) HIV-positive patients were recruited for this study. Cryptococcus antigenemia prevalence in plasma samples of HIV‐positive patients was determined by using Antigen lateral ﬂow assay (CrAg‐LFA) also, and CD4+ Th cell counts and HIV‐RNA levels were quantified from blood specimen. Patients' demographic data, clinical manifestation, and concurrent opportunistic infection were recorded. Result . The sex distributions of study participants were 105(52.5%) male and 94(47.5%) female with an age range of 15–65 (mean 39.42 ± 9) years. All patients had a CD4+ T-cell count <100 cells/ µ l with the median 54 cells/ μ l and median HIV-RNA viral load 2.16 × 10 5 RNA copies/ml (50–3.66 × 10 5 RNA copies/ml); the prevalence of cryptococcal antigenemia was found to be 4% in HIV-positive patients. More than half and two third of CrAg‐positive patients had a CD4 count <25 cells/ μ l and HIV viral load >10, 000 copies/ml, respectively, as well; Tuberculosis, Candidiasis, and herpes zoster are the most often observed concurrent infections while cryptococcal antigenemia is significantly associated with oral candidiasis (p < 0.001 ). Conclusion . Although the advent of ART, early diagnosis of cryptococcosis, and application of antifungal interventions, HIV-induced cryptococcal antigenemia positivity in HIV infected individuals is still the countries' big challenge. Thus, stringent follow-up and case management should be considered.